Transforming the Human Capital in Ukraine: Demographic and Educational Dimensions - Ogay М. Yu. (Statistics of Ukraine, 2025)
The human capital accumulating the population’s knowledge, skills, health, and capabilities is a critically important asset for the economic sustainability and postwar recovery of Ukraine. Amidst the large-scale aggression, a core task is the adequate assessment of its current condition and transformations. In view of the above, the research objective is to conduct a comprehensive analysis of change in the human capital through the prism socio-demographic and educational characteristics of households. The article presents results of an analysis by key dimensions of the human capital transformation: demographic (quantitative and age dynamics, gender composition of households, with reference to migration shifts), demographic (by-industry segregation and barriers for early development of the human capital), and, indirectly, economic (activity and structure of social responsibility of households). Besides that, the research places emphasis on the territorial differentiation of these dimensions between urban and rural settlements. The information base for the research covers data from the nationwide sample survey of the socio-economic conditions of households, held from December 2023 to February 2024, and data from the official sample survey of the living conditions of households, held in 2021 and early 2022. These surveys have a harmonized methodological framework allowing for an adequate assessment of the structural transformation scales. Results of the research showed heavy demographic losses and structural changes. The total number of private households decreased from 14.5 million to 13.6 million, with their average size fallen from 2.6 to 2.3 persons. The most dramatic fall, i.e., 10.9 percentage points, was in the share of households with children younger than 18 (from 37.8% to 26.9%), which is an immediate effect of the external migration. The analysis revealed the increasing gender asymmetry in the social responsibility, with women managing nearly 66% of the households. The economic analysis showed a high vulnerability of the human capital, because 56.9% of the households with working members depended only on one working person, which poses critical social and financial risks. Regarding the educational dimension, the analysis confirmed the existence of a significant high-quality potential of the human capital, because 36.3% of the population either had a higher education diploma or were studying in a higher education institution. Yet, its territorial polarization and professional segregation was found: the high-skilled human capital (STEM, economics) was concentrated in cities, thus increasing their role as drivers of the recovery. A crucial barrier for early development of the human capital is the factor of safety: 17.2% of the parents tended to abandon preschool education for safety-related reasons and due to infrastructure constraints in the rural area. In this case, parents are forced to engage in childcare around the clock, thus shrinking the labor supply by the households. Results of this research lay an empirical background for elaborating a targeted micro-oriented policy for eliminating negative transformations of the human capital. The principal institutional schemes proposed to be stimulation of women’s participation in STEM industries, migrant reorientation programs, smoothing of territorial disproportions, and priority investments in the safe educational infrastructure to support early development of the human capital.